Optimasi Keuntungan Penjualan Kopi Menggunakan Metode Simpleks Pada Coffee Homeland - Dwi Andiyani; Fhesiyach Arthiansal Karubun; Didaktus Baptista Kluman; Rahul Febriansyah; Putra Imanuel Pali; Heru Sutejo (Tamilis Synex: Multidimensional Collaboration, 2025)
Coffee Homeland is a local coffee shop that offers three main products: Kopi Negeri, Kopi Story, and Kopi Guren. In its operations, Coffee Homeland faces limited resources in terms of production time, operational costs, and daily production capacity. Therefore, a quantitative method is needed to determine the most efficient production combination to maximize profit. This study applies the simplex method in linear programming, implemented through the POM-QM for Windows application, to develop an optimal production strategy based on existing constraints. Based on simulation and analysis results, the optimal solution is achieved by producing 13 cups of Kopi Negeri, 6 cups of Kopi Story, and 6 cups of Kopi Guren per day. This combination generates a maximum profit of IDR 506,000 per day. The results also show that the daily production limit is the main active constraint in the optimization, while working time still leaves a slack of 1,292 minutes. Thus, the application of the simplex method has proven effective in supporting strategic decision-making related to production and can serve as a reference for Coffee Homeland management to manage resources more efficiently and increase business profitability.